Association Between Radiological Evidence of Kaplan Fiber Injury, Intraoperative Findings, and Pivot-Shift Grade in the Setting of Acute Anterior Cruciate Ligament Injury. Issue 5 (April 2021) - Devitt, Brian M.; Al'khafaji, Ian; Blucher, Nicola; Batty, Lachlan M.; Murgier, Jerome; Webster, Kate E.; Feller, Julian A.
Background: Biomechanical studies have suggested that the Kaplan fibers (KFs) of the iliotibial band play a role in controlling anterolateral rotation of the knee. There is a paucity of clinical information on whether injury to the KF in the setting of anterior cruciate ligament (ACL) rupture contributes to increased rotatory laxity of the knee. Purpose/Hypothesis: The purpose was to evaluate the association among radiological evidence of KF injury, intraoperative arthroscopic findings, and grade of pivot shift at the time of ACL reconstruction (ACLR). It was hypothesized that KF injury would be associated with increased injury to the lateral compartment of the knee and a higher grade of pivot shift. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective magnetic resonance imaging (MRI) analysis was conducted on 267 patients with ACL-injured knees who underwent primary ACLR. Patients who had MRI and surgery within 60 days of injury were included (mean age, 23.6 years); there were 158 (59.2%) male patients. MRI was performed using standard knee protocols, and diagnostic criteria were applied to identify KF injury. Associations were made among MRI findings, intraoperative findings, and grade of pivot shift with the patient examined under anesthesia at the time of ACLR. A comparison was made between patients with and without radiological evidence of KF injury. Results: The prevalence of KF injury was 17.6% (47/267 patients). Arthroscopic evidence of lateral meniscal injury was associated with KF injury (KF intact, 31%; KF injured, 55%; P = .010). The majority of patients in the intact and injured KF groups had a grade 2 pivot shift (75% and 70%, respectively). A minority had grade 3 pivot shift: 5% in the intact group versus 6.4% in the injured group. There was no association between radiological evidence of KF injury and pivot-shift grade ( P = .600). Conclusion: In acute ACL injury, KF injuries were not very common (17.6%), and the rate of grade 3 pivot shift was low (5.2%). When present, KF injuries were not associated with a higher-grade pivot shift. However, there was an association between KF injury and lateral meniscal tears identified at the time of ACLR. The role of KFS in controlling anterolateral rotatory laxity in the acute ACL injury in the clinical setting may be less evident when compared with the biomechanical setting.